Structural properties and crystallization of sodium tellurite glasses - Šantić, Ana (Array, 2008)
Summary: The structural properties and crystallization behaviour of xNa2O-(100-x)TeO2 (0 <= x <= 33.3, x-% mole fraction) glasses have been investigated by Raman spectroscopy, X-ray diffraction (XRD) and differential scanning calorimetry (DSC). The Raman spectra of glasses show systematic changes in structural units, from TeO4 trigonal bypiramids (tbps) to TeO3 trigonal pyramids (tps) with increasing Na2O content in glass. These structural changes are result of Te–eqOax–Te disruption and the formation of non-bridging oxygens (NBOs) in glass network. When heated at 623 K for 10 h glasses crystallized to different phases: alpha-TeO2, Na2Te4O9 and a new crystalline phase which is believed to be a polymorph of Na2Te2O5